2020
DOI: 10.1155/2020/7523892
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin 6 Attenuates Alloxan-Induced Type 1 Diabetes Mellitus in Mice and Cytokine-Induced Cytotoxicity in RIN-m5F Beta Cells

Abstract: Type 1 diabetes is associated with the destruction of pancreatic beta cells, which is mediated via an autoimmune mechanism and consequent inflammatory processes. In this article, we describe a beneficial effect of peroxiredoxin 6 (PRDX6) in a type 1 diabetes mouse model. The main idea of this study was based on the well-known data that oxidative stress plays an important role in pathogenesis of diabetes and its associated complications. We hypothesised that PRDX6, which is well known for its various biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Investigations by Nano et al have documented protective effects of islet neogenesis associated protein (INGAP) against proinflammatory cytokineinduced metabolic defects, including accelerated NFκB signaling S536 phosphorylation and nuclear accumulation of p65 [70]. Novoselova and coworkers studied potential protective effects of peroxiredoxin 6 (Prx6) against metabolic dysfunction in rat insulinoma RIN-m5F cells following exposure to high glucose or proinflammatory cytokines [71]. Based on data accrued from a series of complementary studies, these investigators surmised that NF-κB signaling module, specifically S536 phosphorylation of p65, as a target for Prx6 mediated protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations by Nano et al have documented protective effects of islet neogenesis associated protein (INGAP) against proinflammatory cytokineinduced metabolic defects, including accelerated NFκB signaling S536 phosphorylation and nuclear accumulation of p65 [70]. Novoselova and coworkers studied potential protective effects of peroxiredoxin 6 (Prx6) against metabolic dysfunction in rat insulinoma RIN-m5F cells following exposure to high glucose or proinflammatory cytokines [71]. Based on data accrued from a series of complementary studies, these investigators surmised that NF-κB signaling module, specifically S536 phosphorylation of p65, as a target for Prx6 mediated protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the insulin-stimulating activity of Prx6 in vitro was detected both when RIN-m5F β-cells were cultivated under normal conditions and under stressful conditions, inducing cell death [99]. In an alloxan-or streptozotocin-induced mouse model of diabetes, intravenous administration of recombinant Prdx6 prevented hyperglycemia, reduced mortality, restored the plasma cytokine profile, and reduced β-cell destruction in the islets of Langerhans in the mouse pancreas [100][101][102].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Systematic studies evaluating the role for Prdx6 in protection against T1D consequences in in vivo and in vitro were conducted. Using alloxan model of severe murine diabetes allowed us to show that the intravenous ly administered recombinant Prdx6 prevents hyper glycemia, decreases mortality rate, restores serum cytokine profile, and reduces destruction of beta cells in the pancreatic islets of Langerhans [79]. Moreover, in vitro experiments with Prdx6 showed that it protects rat insulinoma (RIN m5F) beta cells exposed to TNF α and IL 1β by decreasing ROS production and cell apoptosis.…”
Section: Protective Effects Of Peroxiredoxin 6 In Various Models Of Type 1 Diabetesmentioning
confidence: 99%